The Influence of the Corporate Life Cycle and Sales Growth on Cash Holding with Geographic Diversification as a Moderating Variable (An Empirical Study of Industrial Sector Companies Listed on the Indonesia Stock Exchange) - Mochamad Aditia Rachmawan; Sugiyanto Sugiyanto; Nofryanti Nofryanti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study investigates the influence of the firm life cycle and sales growth on corporate cash holdings, with geographic diversification examined as a moderating variable. Cash holding policy is a strategic financial decision that reflects firms’ responses to operational uncertainty, investment opportunities, and financial constraints, particularly in the context of dynamic industrial sector conditions. This research employs a quantitative approach using panel data from industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The empirical analysis is conducted using Moderated Regression Analysis (MRA) to examine both the direct effects of firm life cycle and sales growth on cash holdings and the potential moderating role of geographic diversification. The results indicate that firm life cycle and sales growth have a significant influence on corporate cash holdings, suggesting that firms’ stages of development and growth dynamics shape their liquidity management strategies. However, geographic diversification does not significantly moderate the relationship between firm life cycle and sales growth on cash holdings. These findings imply that corporate cash holding policies in Indonesian industrial firms are primarily driven by internal firm characteristics rather than by the extent of geographic diversification. The study contributes to the literature on corporate liquidity management by providing empirical evidence from an emerging market context and offers practical implications for managers in formulating cash management strategies aligned with firms’ life cycle stages and growth conditions.